Adefovir dipivoxil induces DNA replication stress and augments ATR inhibitor‐related cytotoxicity. Issue 5 (13th April 2020) - Patel, Agata; Seraia, Elena; Ebner, Daniel; Ryan, Anderson Joseph
Abstract : Replication stress is a common feature of cancer cells. Ataxia telangiectasia‐mutated (ATM) and Rad3‐related (ATR) signalling, a DNA damage repair (DDR) pathway, is activated by regions of single‐stranded DNA (ssDNA) that can arise during replication stress. ATR delays cell cycle progression and prevents DNA replication fork collapse, which prohibits cell death and promotes proliferation. Several ATR inhibitors have been developed in order to restrain this protective mechanism in tumours. It is known, however, that despite other effective anticancer chemotherapy treatments targeting DDR pathways, resistance occurs. This begets the need to identify combination treatments to overcome resistance and prevent tumour cell growth. We conducted a drug screen to identify potential synergistic combination treatments by screening an ATR inhibitor (VE822) together with compounds from a bioactive small molecule library. The screen identified adefovir dipivoxil, a reverse transcriptase inhibitor and nucleoside analogue, as a compound that has increased cytotoxicity in the presence of ATR, but not ATM or DNA‐dependant protein kinase (DNA‐PK) inhibition. Here we demonstrate that adefovir dipivoxil induces DNA replication stress, activates ATR signalling and stalls cells in S phase. This simultaneous induction of replication stress and inhibition of ATR signalling lead to a marked increase in pan‐nuclear γH2AX‐positive cells, ssDNA accumulation and cell death, indicative of replication catastrophe. Abstract : What's new? Replication stress is common in cancer cells, which harness the ATR DNA damage repair pathway as a protective mechanism. Several ATR inhibitors have been developed, but resistance is likely to occur. Here, the authors set to identify potential synergistic combination treatments by screening an ATR inhibitor (VE822) together with compounds from a bioactive small molecule library. The reverse transcriptase inhibitor Adefovir dipivoxil simultaneously induced replication stress and inhibition of ATR signalling, leading to replication catastrophe and cell death. The findings add to the growing evidence that targeting cells under high replication stress can increase cancer cell killing by ATR inhibition.